2019
DOI: 10.1186/s40814-019-0467-9
|View full text |Cite
|
Sign up to set email alerts
|

Return to Everyday Activity in the Community and Home: a feasibility study for a lifestyle intervention to sit less, move more, and be strong

Abstract: Background: Many interventions designed to meet physical activity guideline recommendations focus on a single component (e.g., walking), to the detriment of other elements of a healthy lifestyle, such as reducing prolonged sitting and doing balance and strength exercises (i.e., bundled multiple behaviors). Adopting these multiple health behaviors within daily life routines may facilitate uptake and support longer-term behavior change. We tested feasibility for a three-part lifestyle intervention to support old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…An additional five studies were eliminated because the results did not answer the research question of this review. These included a validity study of another measurement of habit (Boiché et al, 2016 ), a feasibility study with insufficient statistical results (Ashe et al, 2019 ), and studies not reporting habit as an individual variable and its relationship to physical activity (Phillips et al, 2016 ; Duan et al, 2017 ; Howlett et al, 2019 ). One study was excluded, because habit did not refer directly to physical activity but to wearing a Fitbit (Ellingson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…An additional five studies were eliminated because the results did not answer the research question of this review. These included a validity study of another measurement of habit (Boiché et al, 2016 ), a feasibility study with insufficient statistical results (Ashe et al, 2019 ), and studies not reporting habit as an individual variable and its relationship to physical activity (Phillips et al, 2016 ; Duan et al, 2017 ; Howlett et al, 2019 ). One study was excluded, because habit did not refer directly to physical activity but to wearing a Fitbit (Ellingson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Older adults also need to believe they have the capabilities to change their behavior 87 . BCT's such as goal setting 33,39,41,[44][45][46][47]51,55,58,59,[64][65][66]68,69,76,84,[88][89][90][91][92][93][94] , action planning , coping planning 88,93 and motivational interviewing 50,74,89 can be used to increase self-efficacy towards changing SB in older adults.…”
Section: Under What Types Of Motivation Do Which Mechanisms Lead To C...mentioning
confidence: 99%
“…To break the habit of SB, several studies suggested that older adults need to become aware about the automaticity of their behavior 39,46,99 . Providing feedback on behavior and stimulating older adults to monitor their own behavior are frequently used BCT's that might lead to an increased awareness 39,40,45,49,56,62,84,88 . However, only bringing habitual behavior into conscious awareness seems insufficient to generate behavior change 39,49,57 .…”
Section: Under What Types Of Motivation Do Which Mechanisms Lead To C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the rising use of the internet in older adults in Germany (50% of adults aged 60 years and older use the internet on a regular basis [ 33 ]) means that individualized PA programs may be integrated into web-based formats [ 34 ]. As such, older populations may be able to utilize home-based interventions that are offered on a print or web basis [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%